Arginine vasopressin selectively enhances recognition of sexual cues in male humans - Guastella, Adam J.; Kenyon, Amanda R.; Unkelbach, Christian; Alvares, Gail A.; Hickie, Ian B. (Psychoneuroendocrinology, 2011)
Arginine Vasopressin modulates complex social and sexual behavior by enhancing social recognition, pair bonding, and aggression in non-human mammals. The influence of Arginine Vasopressin in human social and sexual behavior is, however, yet to be fully understood. We evaluated whether Arginine Vasopressin nasal spray facilitated recognition of positive and negative social and sexual stimuli over non-social stimuli. We used a recognition task that has already been shown to be sensitive to the influence of Oxytocin nasal spray (Unkelbach et al., 2008). In a double-blind, randomized, placebo-controlled, between-subjects design, 41 healthy male volunteers were administered Arginine Vasopressin (20IU) or a placebo nasal spray after a 45min wait period and then completed the recognition task. Results showed that the participants administered Arginine Vasopressin nasal spray were faster to detect sexual words over other types of words. This effect appeared for both positively and negatively valenced words. Results demonstrate for the first time that Arginine Vasopressin selectively enhances human cognition for sexual stimuli, regardless of valence. They further extend animal and human genetic studies linking Arginine Vasopressin to sexual behavior in males. Findings suggest an important cognitive mechanism that could enhance sexual behaviors in humans.